Relationship Between Sleep Quality and Hypertension Among Working-Age Population in Indonesia - Arwan Setyo Nugroho; Erni Astutik; Ferry Efendi (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2020)
Introduction: One of the diseases which are continuously becoming a public health problem is hypertension. The prevalence of hypertension in working-age or productive age in Indonesia has increased significantly in recent years. There are many risk factors for hypertension in adults, one of which is lack of sleep. Sleep disorders can increase the risk of hypertension. This study aimed at finding out the relationship between sleep quality and the incidence of hypertension among the working-age population in Indonesia. Methods: This study utilized secondary data from the Indonesia Family Life Survey (IFLS) 5 data with a cross-sectional study design. The sample in IFLS 5 was taken using Multistage random sampling. The number of samples was 8,815 with inclusion criteria, which included that respondents were 15-64 years old and had complete data on the variables studied, namely: age, sex, sleep quality, physical activity, Body Mass Index (BMI), smoking habits and hypertension. Data were analyzed using multiple logistic regression. Results: Respondents with poor sleep quality had 1.39 higher odds of experiencing hypertension compared to respondents who had good sleep quality after being controlled by variables of gender, age, smoking status, physical activity, and nutritional status. (Poor-good sleep quality=1.39, 95% CI 1.20-1.61 p=0.000). Conclusions: It is necessary to strengthen information about health promotion regarding the prevention of hypertension in the community, especially good time management, to maintain sleep quality and the need for health programs on prevention of hypertension carried out by the ministry of health to the community through existing health-workers.